2013
DOI: 10.1080/07347332.2012.741092
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perceptions and Quality of Life in Japanese and Dutch Women with Breast Cancer

Abstract: Knowledge on cross-cultural quality of life (QOL) and illness perceptions may help women with breast cancer cope more effectively. The self regulation model (SRM) guided the current exploratory longitudinal pilot-study. Central to SRM is the perception of health threats and their effects on QOL. Illness perceptions and QOL were assessed in 22 Dutch and 21 Japanese patients with breast cancer who filled out questionnaires before, 1 week, and 8 weeks after the first chemotherapy course. The questionnaires assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
4
36
0
1
Order By: Relevance
“…The perceived lack of need of aphasia services seems to stem from more deeply rooted cultural beliefs about age and communication. This is not entirely surprising as cross-cultural differences have been found in perceptions toward communication problems such as voice disorders [71] as well as perceptions of illness [72], recovery [73] and long-term care [74]. In addition, age and culture have been found to influence illness perceptions and adherence to prescribed treatment regimes [75].…”
Section: Dischargementioning
confidence: 92%
“…The perceived lack of need of aphasia services seems to stem from more deeply rooted cultural beliefs about age and communication. This is not entirely surprising as cross-cultural differences have been found in perceptions toward communication problems such as voice disorders [71] as well as perceptions of illness [72], recovery [73] and long-term care [74]. In addition, age and culture have been found to influence illness perceptions and adherence to prescribed treatment regimes [75].…”
Section: Dischargementioning
confidence: 92%
“…For instance, in a study on illness perception among critically ill patients in US, African-Americans tend to be more optimistic compared to Caucasian patients (Ford et al 2010) [21]. Another study on illness perception among breast cancer patients in Netherlands and Japan showed stronger concern about the illness in Japanese subjects [22]. It is crucial for clinicians to be aware of this issue in order to have better communication with patients from different racial backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Within our study the lowest utility scores were often observed in the Japanese cohort, with the exception of the severe renal flare HS and the severe CNS flare HS. Previous studies, not specific to SLE, have shown EQ-5D derived utility scores vary on average by 0.24 between Japan and the UK – this may be due to cultural disparities [ 27 , 28 ]. Differences observed in utility scores may be reflective of differences in social preference weights between populations.…”
Section: Discussionmentioning
confidence: 99%